El arcediano de México don Juan Negrete (siglo xvi): entre el oficio y la disipación - González González, Enrique (2012)
In 1541 Doctor Juan Negrete arrived in Mexico, the first lay professor of theology, and who was also named the archdeacon of the new cathedral. Twelve years later he participated as the first rector in the inauguration of the Royal University of Mexico, and a few months before he died in 1555 he also taught theology there. Several documents relating to Negrete, many of them unpublished, reveal the internal difficulties which the first bishop and the cathedral chapter experienced as they attempted to lay the basis for the secular aspects of the church. Negrete, instead of being a factor of cohesion in the chapter, was the source ofdivisions and conflicts given his disorderly life style and propensity to speak ill of others and initiate rumors. He created many enemies and instigated proceedings which often led to prison. His case in particular reveals the ambivalent nature of many personalities who participated in the creation of Spanish institutions in the newly conquered lands.